Pengaruh Citra Merek Terhadap Keputusan Pembelian Roti Di Cv Lemona Cake & Bakery Tasikmalaya - Deni Permana (PT. Gudang Pustaka Cendekia, 2023)
The purpose of this study is to find out and prove how much influence brand image has on the purchase decision of bakery products in CV. Lemona Cake &Bakery Tasikmalaya. This study uses quantitative methods with an associative approach that is causal aims to determine the influence between independent variables on dependent variables. The population in this study is respondents who have bought bakery products at Lemona Cake &; Bakery Tasikmalaya, while the number of respondents is as many as 97 respondents. In this study using Non Proability Sampling techniques, Non Proability Sampling, namely sample selection with non-probability methods or non-randomly, population elements do not have the same opportunity to be selected as samples. This is done based on the consideration of relatively fast hang times and relatively cheap costs, then the sampling method uses Accidental Sampling, Accidental sampling is a sampling technique based on chance, that is, anyone who accidentally meets the researcher can be used as a sample, if it is considered that the person who happened to meet is suitable as a source of data. From the results of this study shows that the value of t-count obtained is 8.204 and t-table 1.661 it can be seen that t-count is greater than t-table (8.204 > 1.661) so that H0 is rejected and Ha is accepted meaning that the hypothesis is accepted, so it can be explained that brand image has a positive and significant effect on purchasing decisions, with a value I of 0.644 and a value of coefficient of determination (R square) of 0.641 which means the influence of brand image variables (x) on the purchase decision variable (y) is 64.1% while the remaining 35.9% is explained by other factors or variables that are unknown and not included in this study.